The Anthropology of Cultural Heritage in Europe: A Brief Genealogy from the Desk (1970–2020) and Empirical Observations from the Field (2010–2020) - Testa, Alessandro (Traditiones, 2021)
This article offers an overview of the origins and development of the anthropology of cultural heritage in Europe, tracing its main genealogical lineages stemming from kindred disciplines and methods in a comparative fashion. This brief genealogy is then complemented by a set of considerations and observations about the author’s personal ethnographic explorations of various European countries and regions, again with the aim of fruitful comparison. The article discusses how the anthropology of cultural heritage in Europe emerged, where it stands now, and where it might be going.